1983
DOI: 10.1007/bf00214982
|View full text |Cite
|
Sign up to set email alerts
|

Substance P-containing nerve fibres in large peripheral blood vessels of the rat

Abstract: Substance P-immunoreactive nerve fibres were localized by the indirect immunohistochemical method in the adventitia and the adventitial-medial border of large peripheral arteries and veins of the rat. Arteries showed a richer substance P-containing innervation than veins. The superior mesenteric artery was densely innervated, whereas no substance P-containing fibres were found around the carotid artery. Substance P produced a vasoconstriction of the veins, but was basically without effect on arteries, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Role of CGRP and SP in the vascular walls and ILG The occurrence of SP-or CGRP-immunoreactive fibers in association with arteries as well as sympathetic and parasympathetic ganglia is known, and their possible origin has been suggested to be collaterals from primary sensory nerve fibers (BAKER et al, 1980;MATTHEWS and CUELLO, 1982;BARJA et al, 1983;LUNDBERG et al, 1984b;SUZUKI et al, 1989). If the SP-and CGRP-immunoreactive lingual perivascular fibers and CGRP-immunoreactive varicose fibers in the ILG are collaterals of primary sensory neurons, stimulation of the sensory terminals would directly influence vascular function and regulate parasympathetic ganglionic activity by the peripheral axon-reflex mechanisms.…”
Section: Innervation Of Dog Tongue 513mentioning
confidence: 99%
“…Role of CGRP and SP in the vascular walls and ILG The occurrence of SP-or CGRP-immunoreactive fibers in association with arteries as well as sympathetic and parasympathetic ganglia is known, and their possible origin has been suggested to be collaterals from primary sensory nerve fibers (BAKER et al, 1980;MATTHEWS and CUELLO, 1982;BARJA et al, 1983;LUNDBERG et al, 1984b;SUZUKI et al, 1989). If the SP-and CGRP-immunoreactive lingual perivascular fibers and CGRP-immunoreactive varicose fibers in the ILG are collaterals of primary sensory neurons, stimulation of the sensory terminals would directly influence vascular function and regulate parasympathetic ganglionic activity by the peripheral axon-reflex mechanisms.…”
Section: Innervation Of Dog Tongue 513mentioning
confidence: 99%
“…1 Sensory afferent nerves have cell bodies located in the dorsal root ganglia and send efferent processes to a variety of cardiovascular tissues. [2][3][4] It has been established that sensory afferent fibers release a variety of vasodilator neuropeptides, eg, calcitonin gene-related peptide (CGRP) and substance P, in response to local stimuli. 5 These vasodilator neuropeptides chronically released from sensory nerves may play a role in blood pressure regulation because it has been demonstrated that altered synthesis or release of these vasodilator neuropeptides occurs in genetic and experimental hypertensive animal models.…”
mentioning
confidence: 99%
“…In addition to the classical transmitters NE and acetylcholine (ACh), co-transmitters have been identified in perivascular nerves, such as the purinergic component in sympathetic transmission (17), and vasoactive neuropeptides such as substance P (SP) and CGRP have been shown to be present in some blood vessels (18,19). In our experimental system (in guanethidine-treated ring preparations), exogenously added SP (10-6 M); adenosine (2 x 10-6 M), a purine (P1)-receptor agonist; and a,(3-methylene ATP (10-6 M), a purine (P2)-receptor agonist, did not mimic the observed effect of electrical stimulation (Fig.…”
Section: Responses To Electrical Stimulationmentioning
confidence: 99%